2014
DOI: 10.18352/ijc.463
|View full text |Cite
|
Sign up to set email alerts
|

The evolution of self-organizing communication networks in high-risk social-ecological systems

Abstract: Recently published research shows that members of regional communication networks form links based on how risky their exchanges with others may be: low-risk situations favor the creation of bridging structures that solve coordination problems, whereas high-risk situations lead to the establishment of bonding structures that make detection and punishment of defection more likely. This basic expectation has been tested in low-risk regional arenas, where indeed more bridging structures formed in time (Berardo and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
38
0
4

Year Published

2016
2016
2022
2022

Publication Types

Select...
10

Relationship

4
6

Authors

Journals

citations
Cited by 48 publications
(56 citation statements)
references
References 27 publications
4
38
0
4
Order By: Relevance
“…Our findings also build on the closed vs. open network structure debate (and subsequently, the bonding vs. bridging capital debate) that is of increasing importance to the complex governance literature (Berardo, 2014a(Berardo, , 2014bBerardo & Scholz, 2010;Fischer et al, 2014;Ingold & Leifeld, 2014;Shrestha, 2013). We find (as others have) that there is no panacea: the extent to which either structure is advantageous is conditional on the needs of the individual actor and that these needs vary between actors in the same system.…”
Section: Resultssupporting
confidence: 75%
“…Our findings also build on the closed vs. open network structure debate (and subsequently, the bonding vs. bridging capital debate) that is of increasing importance to the complex governance literature (Berardo, 2014a(Berardo, , 2014bBerardo & Scholz, 2010;Fischer et al, 2014;Ingold & Leifeld, 2014;Shrestha, 2013). We find (as others have) that there is no panacea: the extent to which either structure is advantageous is conditional on the needs of the individual actor and that these needs vary between actors in the same system.…”
Section: Resultssupporting
confidence: 75%
“…Their research thus suggests that low‐risk situations are associated with the emergence of bridging structures in networks, as the risk hypothesis predicts. Since then, other research has found additional support for the risk hypothesis (Berardo ; Feiock, Lee, and Park ; Henry and Vollan ; Lee ; Lubell, Robins, and Wang ).…”
Section: Bonding and Bridging Structures Involving Actors And Forumsmentioning
confidence: 95%
“…Many collective action problems can be divided into two broad classes-coordination versus cooperation problems. The former describes a situation where all or most actors agree on what they want to accomplish, and getting there is more a matter of orchestrating the actors' different activities in efficient ways (57). Joint efforts to eradicate an invasive salt-marsh cordgrass species in the San Francisco Bay in California serves as an example of a coordination problem (58).…”
Section: Coordination or Cooperationmentioning
confidence: 99%